A New Material Model for Agglomerated Cork - Gabriel Thomaz de Aquino Pereira; Ricardo J. Alves de Sousa; I-Shih Liu; Marcello Goulart Teixeira; Fábio A. O. Fernandes (Mathematical and Computational Applications, 2022)
It is increasingly necessary to promote means of production that are less polluting and less harmful to the environment following the UN 2030 agenda for sustainable development. Using natural cellular materials in structural applications can be essential for enabling a future in this direction. Cork is a natural cellular material with an excellent energy absorption capacity. Its use in engineering applications and products has grown over time, so predicting its mechanical response through numerical tools is crucial. Classical cork modeling uses a model developed for foam material, including an adjustment function that does not have a clear physical interpretation. This work presents a new material model for an agglomerated cork based solely on well-known hypotheses of continuum mechanics using fewer parameters than the classical model and further a finite element framework to validate the new model against experimental data.